Moderating Effect of CEO Gender Diversity on the Relationship Between Board Academic Qualifications and Earnings Management of Listed Non-Financial Services Sector in Nigeria - Efiong, Eme Joel; Nkiri, Joseph Eyam; Ibrahim Mallam Fali; Odama Patrick Ojeka; Effiong Blessing Andem; Eyibio Affyrock Victor; Mohammed Bukar; Kauji; Hirhyel Ibrahim Abba8 (International Journal of Business and Quality Research, 2025)
This study investigates the influence of board academic qualifications and the moderating effect of CEO gender diversity on earnings management in Nigeria's non-financial services sector. Drawing on a population of 105 listed non-financial firms, a sample of 72 firms was selected over a ten-year period (2013–2022). The study employs a correlational and ex post facto research design, utilizing secondary data obtained from corporate financial statements and the Nigerian Exchange Group website. A longitudinal dataset was constructed and analyzed using panel regression techniques via Stata 17. The findings reveal that both board academic qualifications and CEO gender diversity have a positive and significant association with earnings management. However, CEO gender diversity negatively moderates the relationship between board academic qualifications and earnings management. This suggests that while highly educated boards may be associated with increased earnings management practices, the presence of gender-diverse leadership at the CEO level can mitigate this tendency. The study concludes that board academic qualifications significantly influence earnings management among Nigeria’s non-financial firms, but CEO gender diversity serves as an effective governance mechanism, reducing opportunistic financial reporting behaviors. Accordingly, the study recommends that regulatory authorities and shareholders actively promote gender diversity, particularly at the CEO level, to enhance corporate governance structures and discourage earnings management. Additionally, firms should incorporate ethical leadership training into board development initiatives to complement academic expertise with sound ethical judgment.